(untitled) (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Astirin OP, Pitoyo A, Hidayat A, Astuti AY, Rahmawati WM, Nurcahyo RW. 2025. Biodiversity and conservation status of flora and fauna in Magetan, East Java, Indonesia: A focus on rare and protected species of mammals, birds and plants. Biodiversitas 26: 1606-1617. Indonesia is recognized for its high level of species endemicity across its islands, but this biodiversity is under significant threat due to high loss rates. Magetan District, East Java Province, Indonesia comprises 8% of protected areas, located adjacent to Mount Lawu, which harbor substantial biodiversity. This study aims to assess the diversity, distribution and protection status of wildlife in Magetan, based on the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES) and the Minister of Environment and Forestry Regulation of the Republic of Indonesia, especially for mammals, birds and plants. The research utilized a combination of methods, including the collection of biodiversity data from 2013 to 2022, interviews with relevant stakeholders, and field observations. The findings identified three mammalian species and one plant listed under CITES Appendix I. Additionally, 19 wild animal species and one plant species were found to be rare and protected under the government regulation. Among these, five species belong to the mammal group, while 14 species are avifauna group. The highest concentrations of these protected species were observed in the Panekan and Plaosan Sub-districts, highlighting the importance of these two areas for conservation. Conservation strategies are required to protect these animals and plants by avoiding deforestation and habitat restoration. Other conservation strategies are by enforcing laws, addressing human-wildlife conflicts, raising awareness, and conducting regular monitoring. The study provides critical insights for conservation policy development and biodiversity documentation, specifically for Magetan District.